Analisis Pengelolaan Arsip Dinamis dalam Sistem Kearsipan di PT X - Marsofiyati Marsofiyati; Erikha Ardya Marghifa; Christian Wiradendi Wolor (Universitas 45 Surabaya, 2023)
This study aims to analyze the management of archives in the archive system, identify the obstacles that occur in the management of archives, and identify factors that influence the management of archives at PT X. The research method used in this research is a descriptive qualitative research method with a case study approach. Data collection techniques used in this study were observation, interviews, documentation and literature studies. The results of this study indicate that the implementation of regulations regarding guidelines for the management of dynamic records at PT X has not been fully effective. Management of dynamic records in one work unit consists of creating archives, recording and filing records, storing records, using archives, maintaining records, and depreciating records. As well as there are several obstacles and factors that influence the management of dynamic archives in the work unit.